Tilo miya Uranus per - Yasmin Mutasim Barjees (Karachi: Children Publications)
"Tilo Miya Uranus Per" is an engaging and imaginative Urdu book written by Yasmin Mutasim, which blends humor, fantasy, and social commentary in a unique way. The book revolves around the fictional character Tilo Miya, who embarks on a whimsical journey to Uranus, one of the planets in our solar system. The story is a mix of adventure and satire, with Tilo Miya being a comical character who finds himself in a completely different world. As he explores Uranus, the planet is depicted as a place full of strange and amusing creatures, bizarre environments, and unexpected situations. Through these fantastical elements, the author uses humor to reflect on human nature, societal issues, and the complexities of life.
"Tilo Miya Uranus Per" combines entertainment with deeper insights, making it both enjoyable and thought-provoking. Yasmin Mutasim$1 (Bs witty writing style, along with her imaginative storytelling, engages readers while also offering them a chance to reflect on the quirky and sometimes absurd nature of human existence.s
Keywords: Science Fiction; Humor and Satire